Complete Midwifery Care In Very High-Risk Pregnancy - Dintya Ivantarina; Dwi Yuliawati; Fitri Yuniarti; Wulan Anggraini (Science Midwifery, 2021)
A very high-risk pregnancy is a risk group for pregnant women with the highest number of maternal and neonatal deaths. One way that can be carried out to prevent maternal and infant complications is to provide complete midwifery care. The purpose of this case study is to provide complete midwifery care to Mrs. "W" from pregnancy to family planning. The research design used is a case study with the research subject of Mrs. ”W”. Methods of collecting data through interviews, observation, and documentation studies. The results of midwifery care for Mrs. ”W” found data during pregnancy classified as very high-risk pregnancy with a Poedji Rochjati score of 14 (anemia, height < 145 cm, and a history of childbirth with infusion). Problems during pregnancy are the lack of adequate nutrition and optimal rest as well as the discomfort of swollen legs and back pain. During labour, the diagnosis of premature rupture of membranes was obtained. In the puerperium, the problem of suture wound pain was found. During the newborn period, jaundice was diagnosed. During family planning, the mother chose 3 months of injectable contraception. Management was given according to the diagnosis and problems found from the time of pregnancy to family planning. Complete midwifery care can increase the effectiveness of health care for the mother as a whole so that it does not endanger the mother and baby and increase patient satisfaction in getting midwifery services.